The fundamental right of access to justice and institutional policies of the Judiciary in the fight against corruption in Peru - Vásquez Rojas, Deysy Elizabeth (2021)
Addressing the problem of corruption in the administration of justice in Peru is a complex task, especially when it is an established, structural and historical practice. The study analyzes the scope of the fundamental right of access to justice, as well as an approach to the problem of corruption in the judicial sphere in Peru. It also analyzes judicial proceedings and identifies the progress made in institutional policies and the challenges pending for the Judiciary, as well as the implications of this problem concerning the right to access to justice.